Keys don't grow in threes - FARRELL, STEPHEN (IEEE, 2009)
Many Internet security mechanisms depend on the use of cryptographic algorithms for various forms of authentication and confidentiality. Even when well-known and standardized cryptographic algorithms are used in well-known protocols, some parameters must be specified, the most important of which are usually algorithm identifiers and key or hash-output lengths. The author reviews some recent key length recommendations and compares those to current usage. He raises some issues that come up once we start to do the updates called for by various cryptographic experts and authorities who've made recommendations on this topic - some of which call for widespread changes to occur in 201
PUBLISHED
Keywords: Internet security mechanisms; cryptographic algorithms